Magneto-fluidics microchip - Lee, June Meng Suan (2014)
With the present advancement of microfabrication technologies, substantial growth in Biomedical Microelectromechanical Systems (BioMEMS) is significantly huge. Incorporation of the magnetism techniques with microfluidics, diverse biological related applications and innovations like metastatic cancer cell removal could be achieved; in the aspect of lab-on-a-chip.